Peanut (Arachis hypogaea) Milk Vegan Cheese with Pineapple (Ananas comosus) Bromelin Enzyme as Coagulant and Carrot (Daucus carota) Extract as Source of Antioxidants - As-Syauqi, Syarifah Miftahqillah; Zulfa, Indana; Nafsiyah, Zakiyatun; Okina, Muhammad Syahrul Rizki; Isnawati, Isnawati (International Journal of Biosciences and Biotechnology; Vol 11 No 2 (2024): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2024.v11.i02.p04, 2024)
Cheese has existed since ancient greece and became one of the fermented foods favored by the community. Cheese is obtained through the process of protein coagulation with the help of bacteria, enzymes, and acids. Increasingly accompanied by technological developments appear various types and preparations of cheese. Cheese is generally made from the milk of cows, goats, horses, and some other animals. But for the development of making cheese made from plants or plants is very rarely found. Making vegan cheese from peanut juice with coagulant enzyme, bromelin, pineapple and extra carrots as a source of antioxidants is present as a new cheese product. Antioxidants function as protectors of the body from free radicals that cause various diseases. To determine the content in vegan cheese made from peanut juice and the addition of carrot extract as a source of antioxidants, organoleptic tests were carried out, protein content tests using the biuret method, and antioxidant tests using DPPH solution. From the results of organoleptic tests carried out get a like response and in the protein content test, it was found that the use of peanut base ingredients has a higher level of protein content than the use of cow's milk base ingredients in cheese making. But in the test of antioxidant levels found that the addition of extra carrots had little affect antioxidant levels in cheese. This happens because the carrot extract present in vegan cheese undergoes oxidation.